2015
DOI: 10.17265/2162-5263/2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 17α-Ethinylestradiol on the Time Needed for Males and Females of Gammarus tigrinus Sexton, 1939 to Re-couple

Abstract: Abstract:The aim of presented study was to determine the behavioural response of precopulatory pairs of Gammarus tigrinus exposed to the 17α-ethinylestradiol (EE2). It was hypothesized that 17α-ethinylestradiol would increase the time needed for a male to re-capture a female. Hypothesis was tested in a laboratory with 20 precopula pairs exposed to different treatment conditions. Paired animals were exposed to two different compound concentrations of 50 ng·L -1 and 500 ng·L -1. The control and solvent control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As E1 is estimated to have 85% of the efficiency of E2 in endocrine disruption [44], the concentrations measured in these rivers can be well above those recommended by the European Commission [14] for E2 and are higher than some independent predictions for no-effectexposure level, which are as low as 6 ng/L for E1 [45]. Estrogens affect the physiological responses of some molluscs, resulting in feminisation and reproductive disruption [3,46], as well as the reproductive behaviour of crustaceans [47]. Moreover, the effects of EDCs in the aquatic environment…”
Section: Evaluation Of E1 Levels In Environmental Water Samplesmentioning
confidence: 78%
“…As E1 is estimated to have 85% of the efficiency of E2 in endocrine disruption [44], the concentrations measured in these rivers can be well above those recommended by the European Commission [14] for E2 and are higher than some independent predictions for no-effectexposure level, which are as low as 6 ng/L for E1 [45]. Estrogens affect the physiological responses of some molluscs, resulting in feminisation and reproductive disruption [3,46], as well as the reproductive behaviour of crustaceans [47]. Moreover, the effects of EDCs in the aquatic environment…”
Section: Evaluation Of E1 Levels In Environmental Water Samplesmentioning
confidence: 78%
“…For instance, in Gammarus tigrinus significant separation effects only at near lethal ethinylestradiol concentrations (Wisniewska and Szaniawska, 2015). Watts et al (2001) observed no effect of environmentally relevant concentrations of the xenoestrogens ethinylestradiol (EE) and bisphenol A on pair re-forming of G. pulex, so the reported effect of other environmental contaminants is particularly interesting.…”
Section: Discussionmentioning
confidence: 99%